Coordinated Cluster/Double Star and ground-based observations of dayside reconnection signatures on 11 February 2004 - La Hoz, Cesar; Zhang, Q. H.; Dunlop, M. W.; Liu, R. Y.; Yang, H. G.; Hu, H. Q.; Zhang, B. C.; Lester, M.; Bogdanova, Y. V.; McCrea, I. W.; Hu, Z. J.; Crothers, S. R.; et al. (Annales Geophysicae, 2011)
A number of flux transfer events (FTEs) were observed between 09:00 and 12:00UT on 11 February 2004, during southward and dawnward IMF, while the Cluster spacecraft array moved outbound through the northern, highaltitude cusp and dayside high-latitude boundary layer, and the Double Star TC-1 spacecraft was crossing the dayside low-latitude magnetopause into the magnetosheath south of the ecliptic plane. The Cluster array grazed the equatorial cusp boundary, observing reconnection-like mixing of magnetosheath and magnetospheric plasma populations. In an adjacent interval, TC-1 sampled a series of sometimes none standard FTEs, but also with mixed magnetosheath and magnetospheric plasma populations, near the magnetopause crossing and later showed additional (possibly turbulent) activity not characteristic of FTEs when it was situated deeper in the magnetosheath. The motion of these FTEs are analyzed in some detail to compare to simultaneous, poleward-moving plasma concentration enhancements recorded by EISCAT Svalbard Radar (ESR) and “polewardmoving radar auroral forms” (PMRAFs) on the CUTLASS Finland and Kerguelen Super Dual Auroral Radar Network (SuperDARN) radar measurements. Conjugate SuperDARN observations show a predominantly two-cell convection pattern in the Northern and Southern Hemispheres. The results are consistent with the expected motion of reconnected magnetic flux tubes, arising from a predominantly sub-solar reconnection site. Here, we are able to track north and south in closely adjacent intervals as well as to map to the corresponding ionospheric footprints of the implied flux tubes and demonstrate these are temporally correlated with clear iono-Correspondence to: Q.-H. Zhang (zhangqinghe@pric.gov.cn) spheric velocity enhancements, having northward (southward) and eastward (westward) convected flow components in the Northern (Southern) Hemisphere. The durations of these enhancements might imply that the evolution time of the FTEs is about 18–22 min from their origin on magnetopause (at ...